The Benefits, Effectiveness, and Risks of ShopeePay: Shaping Consumer Interest - Budiman, Arief; Laksana, Rio Dhani; Aydogmus, Ilkay (Universitas Medan Area, 2025)
This study examines how perceived benefits, system effectiveness, and perceived risks shape consumer interest in using ShopeePay as a digital payment platform in Indonesia. As digital payment adoption accelerates, understanding the key determinants of user preference becomes increasingly important for service providers. Data were collected from 185 active ShopeePay users through a structured question-naire and analyzed using multiple linear regression. The findings reveal that system effectiveness and perceived risks significantly influence consumer interest, whereas perceived benefits do not show a meaningful impact. These results suggest that users prioritize operational performance, transaction reliability, and security considerations over general convenience when evaluating digital payment plat-forms. This study contributes to the business and consumer behavior literature by offering empirical insights into the factors that drive e-wallet usage. Practical implications highlight the importance for fin-tech providers to strengthen service efficiency, enhance security features, and communicate system reliability to improve user engagement and competitive positioning.